Studi Persepsi Pengguna Aplikasi Samsat Digital Nasional (Signal) Sebagai Aplikasi Pelayanan Pajak Kendaraan Bermotor Menggunakan Usability Testing - Novia Angelita Margaretha Silitonga; Kristian Widya Wicaksono (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The advancement of information technology has accelerated the digital transformation of public services through the National Digital Samsat (SIGNAL) application, which facilitates online motor vehicle administrative services. However, the success of the application depends not only on its features but also on its usability, which should ensure ease of use, efficiency, and user satisfaction. Therefore, this study aims to evaluate the application's quality from the users' perspective by describing the usability level of the iOS/App Store version of the SIGNAL application and identifying the Nielsen usability attribute with the highest and lowest user ratings. This study employed a quantitative approach with a descriptive research design based on Jakob Nielsen’s usability framework, consisting of learnability, efficiency, memorability, errors, and satisfaction. Involved 131 users of the iOS/App Store version of the SIGNAL application in Indonesia. Primary data were collected through a questionnaire and analyzed using univariate analysis. The results indicate that the SIGNAL application is relatively easy to learn and provides a satisfying user experience. However, users still encounter issues related to service efficiency, remembering the application workflow, and error handling. Overall, the SIGNAL application demonstrates a good level of usability and supports the digital transformation of public services. Nevertheless, improvements in system stability, service efficiency, and error-handling mechanisms are needed to enhance service quality, improve user experience, and encourage wider public adoption.